Welcome to GreeneMath.com, your source for free math help!
Polynomial Functions Test
About Polynomial Functions:

When we work with functions, we use a very specific notation to ask for the functions value given a certain input for the independent variable. Additionally, we will be looking at two new scenarios: adding/subtracting two polynomial functions and multiplying/dividing two polynomial functions.

Test Objectives:

•Demonstrate the ability to use function notation

•Demonstrate the ability to add/subtract polynomial functions

•Demonstrate the ability to multiply/divide polynomial functions

Polynomial Functions Test:




#1:


Instructions: Perform each indicated operation.


a) $$g(x) = -5x^3 - 7x + 1$$ find: $$g(0),~g(-1), ~g(-3)$$

Watch the Step by Step Video Solution  
|
   View the Written Solution



#2:


Instructions: Perform each indicated operation.


a) $$f(x) = 7x^3-9x+4$$ $$h(x) = 12x^3 + 6x$$ $$g(x) = -19x^3 + 2x^2 - 5$$ find: $$(f + h + g)(x)$$ $$(f + h + g)(-2)$$

Watch the Step by Step Video Solution  
|
   View the Written Solution



#3:


Instructions: Perform each indicated operation.


a) $$f(x) = -5x^3-13x^2+2x-12$$ $$g(x) = 5x^3 - x^2 - 13x$$ $$h(x) = -9x^3 - 10x^2 + x + 10$$ find: $$(f - g - h)(x)$$ $$(f - g - h)(-1)$$

Watch the Step by Step Video Solution  
|
   View the Written Solution



#4:


Instructions: Perform each indicated operation.


a) $$f(x) = 3x$$ $$g(x) = 6x - 6$$ $$h(x) = 7x + 4$$ find: $$(fgh)(x)$$ $$(fgh)(-1)$$

Watch the Step by Step Video Solution  
|
   View the Written Solution



#5:


Instructions: Perform each indicated operation.


a) $$f(x) = 7x^3 - 24x^2 + 16x - 21$$ $$g(x) = x - 3$$ find: $$\frac{f}{g}(x)$$ $$\frac{f}{g}(-5)$$

Watch the Step by Step Video Solution  
|
   View the Written Solution



Written Solutions:




#1:


Solution:


a) $$g(0) = 1$$ $$g(-1) = 13$$ $$g(-3) = 157$$

Watch the Step by Step Video Solution



#2:


Solution:


a) $$(f + g + h)(x) = 2x^2 - 3x - 1$$ $$(f + g + h)(-2) = 13$$

Watch the Step by Step Video Solution



#3:


Solution:


a) $$(f - g - h)(x) = -x^3 - 2x^2 + 14x - 22$$ $$(f - g - h)(-1) = -37$$

Watch the Step by Step Video Solution



#4:


Solution:


a) $$(fgh)(x) = 126x^3 - 54x^2 - 72x$$ $$(fgh)(-1) = -108$$

Watch the Step by Step Video Solution



#5:


Solution:


a) $$\frac{f}{g}(x) = 7x^2 - 3x + 7$$ $$\frac{f}{g}(-5) = 197$$

Watch the Step by Step Video Solution